Investing in partnerships and capacity for impact - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
The core of the CCAFS theory of change for achieving impact is centred on “partnerships” and “capacity”. Without a heavy focus on these, achieving impact at scale is not feasible. Vermeulen and Campbell (2015) propose principles for agricultural research for development (AR4D), one of which is “Allocate resources in three thirds – needs, research, capacity” – an effective AR4D program invests a third of resources in working with next users to build relationships and to define their needs from research, a third on research itself (often with partners), and a third on enhancing next users’ capacity so as to improve the uptake of the research. Another principle is “Invest in, and monitor, capacity enhancement”: an effective AR4D program supports next users, as well as research partners, to enhance their capacities to ask better questions of science, achieve associated development outcomes, and adapt to new knowledge.